Хвороба Іценка-Кушинга: випадок із лікарської практики - Ляшук, П. М.; Станкова, Н. І.; Леонова, М. О.; Бойко, І. В.; Ляшук, Р. П. (Clinical Endocrinology and Endocrine Surgery, 2010)
The article covers a case of Cushing’s disease (hypercorticism). In the clinical findings along with typical features was dominated a relatively rare thromboembolic syndrome. Removal of hypophysical microadenoma contributed to the reverse evolution of the symptoms of the disease.